2005
DOI: 10.2355/isijinternational.45.609
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Behavior of Dioxins and Some Relating Elements in Iron Ore Sintering Bed by Quenching Pot Test

Abstract: Understanding of the formation mechanism of dioxins in the sintering bed is of importance in developing countermeasures to reduce the emission of dioxins from sintering plants. This research has clarified the behavior and the possible mechanism of dioxin formation and the relation to Cl and Cu components in the sintering bed by conducting a series of quenching tests utilizing sintering pots.The progress of flame front was quenched by terminating the air supply, then introducing N 2 gas in the reverse direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 11 publications
2
28
0
Order By: Relevance
“…It might be because the involved raw materials for the iron ore sintering process, such as iron ore and return fines, were abundant in both K + , and Na + (Cieplik et al, 2003;Nakano et al, 2005). The above results were also comparable to that conducted by Tsai et al (2007).…”
Section: Ionic Constituents Containing In Wb Dustssupporting
confidence: 77%
See 3 more Smart Citations
“…It might be because the involved raw materials for the iron ore sintering process, such as iron ore and return fines, were abundant in both K + , and Na + (Cieplik et al, 2003;Nakano et al, 2005). The above results were also comparable to that conducted by Tsai et al (2007).…”
Section: Ionic Constituents Containing In Wb Dustssupporting
confidence: 77%
“…Several laboratory studies have used alkali chlorides as raw material additives (act as catalysts and chlorine sources) to investigate the formation of PCDD/Fs during iron ore sintering process. They found that the alkali chlorides, such as NaCl and KCl, might catalyze the de novo synthesis (Kasai et al, 2001b;Cieplik et al, 2003;Kuzuhara et al, 2003;Nakano et al, 2005). Table 2 show the comparison between the amounts of alkali chlorides added in the above reference studies and the contents of K + , Na + and Cl -found in the present study.…”
Section: Ionic Constituents Containing In Wb Dustsmentioning
confidence: 94%
See 2 more Smart Citations
“…De novo synthesis is proposed as the dominant PCDD/F formation mechanism due to PCDF mean concentrations in the stack flue gas are generally higher than those of PCDD representing over 80% of the total concentration (Wang et al, 2003b;Aries et al, 2006;Sun et al, 2016). Nakano et al (2005), concluded that the dry zone layer was the primary area of PCDD/F formation in the sinter plant. The temperature range within this layer is between 100 to 1000°C (Arion et al, 2002), with presence of carbonaceous material from the coke and/or soot from the ESP when recycled.…”
Section: Pcdd/f Emissions From Sintering Plantsmentioning
confidence: 99%